2018
DOI: 10.1136/jech-2018-211051
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of BMI development between 10 and 42 years of age and their determinants in the 1970 British Cohort Study

Abstract: BackgroundMixture modelling is a useful approach to identify subgroups in a population who share similar trajectories. We aimed to identify distinct body mass index (BMI) trajectories between 10 and 42 years and investigate how known early-life risk factors are related to trajectories.MethodsSample: 9187 participants in the 1970 British Birth Cohort Study, with BMI observations between 10 and 42 years and data on birth weight, parental BMI, socioeconomic status, breast feeding and puberty. Latent growth mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
4
7
0
Order By: Relevance
“…The low-increasing group, with baseline BMI around 20 kg/m 2 , increased slowly during the 20–60 years period, while the high-increasing group with lower baseline BMI increased rapidly. Some studies, using data from China, the UK and Finland, explored BMI trajectories for childhood and early adulthood, showed that BMI may have 2–6 trajectories 13 14 20–25. Though the numbers of trajectories were different among these studies, they all discovered a low-increasing or low-stable group and a high-increasing group, 13 1420–25 which was in line with our results.…”
Section: Discussionsupporting
confidence: 90%
“…The low-increasing group, with baseline BMI around 20 kg/m 2 , increased slowly during the 20–60 years period, while the high-increasing group with lower baseline BMI increased rapidly. Some studies, using data from China, the UK and Finland, explored BMI trajectories for childhood and early adulthood, showed that BMI may have 2–6 trajectories 13 14 20–25. Though the numbers of trajectories were different among these studies, they all discovered a low-increasing or low-stable group and a high-increasing group, 13 1420–25 which was in line with our results.…”
Section: Discussionsupporting
confidence: 90%
“…The mean trajectory duration (time between first and last anthropometric measurement) was 29.2 years (SD = 17.1). 22 studies that began growth assessment in childhood 5,14,18,20,22,30–32,36,38,41–51 and extended into adulthood. Of these 22 studies with growth trajectories beginning in childhood, five studies 20,22,38,41,51 had measures until young adulthood (19–23 years old), 12 studies 16,30–32,36,42–50 had measures until midadulthood (38–50 years old), and five studies 5,14,17,18,46 had measures until older adulthood (60–80 years old).…”
Section: Resultsmentioning
confidence: 99%
“…22 studies that began growth assessment in childhood 5,14,18,20,22,30–32,36,38,41–51 and extended into adulthood. Of these 22 studies with growth trajectories beginning in childhood, five studies 20,22,38,41,51 had measures until young adulthood (19–23 years old), 12 studies 16,30–32,36,42–50 had measures until midadulthood (38–50 years old), and five studies 5,14,17,18,46 had measures until older adulthood (60–80 years old). The remaining studies ( n = 37) 15,19,21–29,33–35,37,39,40,52–72 did not include any childhood measures, and only included measures >18 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, future research should investigate the utility of such efforts that focus on weight-and appearance-change behaviors, particularly weight gain attempts, as well as considering populations for whom these efforts may have particular applicability (i.e., adolescent boys and young adult men). However, despite an overall dearth of research explicitly exploring weight gain attempts among men in middle-and older-adulthood (Brown & Lavender, 2021), it is notable that men in these older age groups do experience body dissatisfaction, including concerns related to perceived reductions in athleticism and muscularity (Lodge & Umberson, 2013), which may be driven by natural weight gain as one ages (Chu et al, 2021;Viner, Costa, & Johnson, 2019;Yang et al, 2021). As such, this warrants additional research to inform a Race/ethnicity categories in each country as per census questions asked in each country: Australia: majority = only speaks English at home, minority = speaks a language besides English at home; Canada: majority = "White (European descent)," minority = any other race/ ethnicity; Mexico: majority = nonindigenous, minority = indigenous; United Kingdom: majority = "White," minority = any other race/ethnicity; United States: majority = "White," minority = any other race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%